Formation of Personnel Potential through Development of Human Resource for Supply Chain Managements on the Example of Training Program of Government - Tatiana Anatolyevna Evstratova; Elena Evgen'evna Kabanova; Ekaterina Alexandrovna Vetrova; Polina Veacheslavovna Palehova; Valentina Ivanovna Kataeva (International Journal of Supply Chain Management, 2019)
Abstract- the main objective of the current research us to present the critical parameters for an effective Human Resources Management policy and potential practical steps for improvements inlogistics and supply chain management (SCM). Effective Human resource management is a critical element of successful organizational operations. Planning a training program to support human resources (HR) functions in an organizational setting involves assessing the need, designing the materials to support human resource professionals, developing the training program, implementing the program and evaluating the impact of the program on departmental operational metrics. The state and society are interested in youth as an active social force, involved in public life and as a participant in social progress. The proper human resource management is needed for the supply chain of the training system in government activities. Participation in the political life of the country contributes not only to representing the interests of young people at the level of whole society, but also attracting the younger generation in managing affairs of the region and the state. This will help the most talented and enterprising young people to express themselves, to gain practical management and decision-making skills. This will also create a new generation of managerial personnel, to be replaced with the current leaders. The Resolution of the Moscow Government dated on November 29, 2005 No. 962-PP entitled “On additional measures to improve work with youth and students in the city of Moscow” provided a new impetus for development of youth policy under the human resource policy. Successfully implementation of the human resource for supply chai managements in projects such as "Youth Chamber" at the Moscow City Duma and the "Student Government Doubles", were aimed to harmonize the socially significant interests of young citizens, youth organizations and executive authorities of the city of Moscow to address the economic and social development of the city.